Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/meg.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with complications in cirrhotic patients undergoing endoscopic retrograde cholangio-pancreatography

Abstract: Outcomes after ERCP in patients with cirrhosis are similar to those of noncirrhotics despite the alteration in coagulation parameters and the presence of disease-specific complications; however, a more cautious approach in patients with cirrhosis undergoing sphincterotomy and MELD of more than 16 is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…8,9 Subgroup analysis showed an increased risk of adverse events only in patients with decompensated cirrhosis. 8,9 Nevertheless, another two studies showed increased overall adverse events in cirrhotic patients compared with noncirrhotic patients. 10,12 Therefore, the risk of an adverse event in patients with cirrhosis is controversial.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,9 Subgroup analysis showed an increased risk of adverse events only in patients with decompensated cirrhosis. 8,9 Nevertheless, another two studies showed increased overall adverse events in cirrhotic patients compared with noncirrhotic patients. 10,12 Therefore, the risk of an adverse event in patients with cirrhosis is controversial.…”
Section: Discussionmentioning
confidence: 98%
“…12 Again, details of EV, including the case number of patients with EV and high-risk EV, were not revealed in previous studies. [8][9][10][11][12] We found no esophageal variceal bleeding during and after diagnostic or therapeutic ERCP, even in those with high-risk EV. Interestingly, one patient with concomitant gastro-EV experienced gastric variceal bleeding 2 days after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These studies consistently showed that patients with higher CP scores had more complications overall. [22][23][24][25] Li et al [8] reported 46 cases of choledocholithiasis treated with ERCP in patients with cirrhosis and found that the incidence of clinically significant bleeding after ERCP was very high (25%) for patients with CP score C. Another study found that the amount of blood loss for patients with cirrhosis and CP score C was significantly higher than that for those with CP score A or B. [26] Patients with cirrhosis may develop varicose veins in the duodenum, which may increase the risk of bleeding after sphincterotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhotic patients have a comparable rate of adverse events of ERCP to noncirrhotic patients. [ 34 ] Overall, ERCP can be conducted safely in cirrhotic patients, and the risk of postprocedural bleeding may be improved in large and medium-sized endoscopy centers that regularly perform ERCP. [ 11 , 18 ] In addition, the overall rate of complications was 9.1% in patients with cirrhosis, and the 30-day procedure-related complications included PEP (4.6%), cholangitis (2.8%), bleeding (1.1%), aspiration pneumonia (0.9%), perforation (0.4%), and bile leak (0.2%).…”
Section: Discussionmentioning
confidence: 99%